2015
DOI: 10.1016/j.mmcr.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Conidiobolus incongruus in a dog: A case report and literature review

Abstract: Conidiobolomycosis is a rare fungal disease of both humans and animals, occurring mainly in tropical and subtropical climates. We describe a disseminated fungal infection in a young, apparently immunocompetent dog who initially presented for antibiotic resistant pneumonia. Histopathology and mycology identified a Conidiobolus sp., further confirmed as Conidiobolus incongruus through DNA sequencing of D1/D2 regions. This is the first report of this species causing disease in dogs and the fifth reported infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 21 publications
0
10
0
7
Order By: Relevance
“…However, this agent has medical importance (EL-SHABRAWI et al, 2014) and it was reported in ovine in Australia (KETTERER et al, 1992;CARRIGAN et al, 1992) and in dogs in United States of America (MACKEY et al, 2015).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…However, this agent has medical importance (EL-SHABRAWI et al, 2014) and it was reported in ovine in Australia (KETTERER et al, 1992;CARRIGAN et al, 1992) and in dogs in United States of America (MACKEY et al, 2015).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Ha sido reportada en: caballos, personas, mulas, venados, llamas, perros, delfines, mandriles, ovejas y chimpancés (Bauer et al 1997;Stephens & Gibson 1997;Robinson et al 2007;Silva et al 2007;Vilela et al 2010, do Carmo et al 2013Ubiali et al 2013). Es causada por la infección del hongo del género Conidiobolus a nivel de la mucosa y submucosa respiratoria (Schumacher & Schumacher 2007;Mackey et al 2015), siendo Conidiobolus coronatus, Conidiobolus incongruus y Conidiobolus lamprauges las principales especies involucradas (Robinson et al 2007). En los caballos, llamas y humanos, la conidiobolomicosis no tiene diseminación sistémica (Bauer et al 1997;Stephens & Gibson 1997;Robinson et al 2007;Silva et al 2007;Vilela et al 2010, do Carmo et al 2013Ubiali et al 2013).…”
unclassified
“…En caballos, las infecciones causadas por Conidiobolus coronatus se localizan en la nasofaringe, con o sin diseminación local hacia los tejidos de la cara, la región retrofaríngea, los senos maxilares, bolsas guturales, tráquea, paladar blando, espacio retrobulbar, o sistema nervioso central (Miller & Campbell 1984;Steiger & Williams 2000;Robinson et al 2007;Schwarz et al 2009;Cafarchia et al 2013;Mackey et al 2015).…”
unclassified
See 2 more Smart Citations